Penggunaan terapi dzikir untuk menurunkan skala nyeri pada pasien post operasi fraktur: studi kasus - Vindi Tantri Astuti (Sahabat Publikasi Kuu, 2023)
Background: Fractures are when a person experiences a fall, trauma, due to a direct blow or due to weakness in the bone itself which causes the continuity of the bone to be broken. Complaints in postoperative patients are pain felt due to surgical wounds. Purpose: To determine the use of dhikr therapy to reduce pain scale in postoperative fracture patients. Method: this type of research is a case study. This study focuses on the application of dhikr therapy to reduce pain scale in postoperative fracture patients. Results: There were 2 patient who experienced a decrease in pain scale after the application of dhikr therapy. The results of the study showed that there was an effect of the pain scale from before and after dhikr therapy in 2 cases of postoperative fracture. Conclusion: Dhikr therapy can reduce pain on the pain scale in post-fracture surgery patients.